Surface changes of gold electrodes produced by periodic potential treatments in hydrofluoric acid solutions - Galindo, M. C. (1989)
The surface changes produced on Au in HF solutions by applying relatively fast periodic potentials are investigated. The range of frequency and potential limits can be adjusted to produce principally either transient activation for the hydrogen electrode reaction (HER) or electrochemical faceting. The first effect is largely independent of the second one, as it implies the development of a transient surface structure which facilitates hydrogen adsorption and absorption. Electrochemical faceting caused by oxidationreduction cycles (ORC) depends on the potential limits which are associated with either Au electrodissolution and electrodeposition or Au oxide electroformation and electroreduction. Electrochemical faceting can be clearly seen through SEM micrographs, and the type of preferred orientation can be tentatively inferred from voltammetry of underpotential deposition (upd) of Pb in 10'3 M Pb(ClO4)2 + 1 M HClO4 solution through a direct comparison with data reported in the literature for the reaction on single-crystal Au surfaces. Electrochemical faceting implies a simultaneous increase in surface roughness, as followed from changes in voltammetric charges for both upd Pb and 0 atom electrodesorption in acid solutions.